Spatial Analysis of Physical Quality of Rural Housing in Iran - mohammad hajipour; Vahid riahi; hadi gharagozloo (تحقیقات کاربردی علوم جغرافیایی)
Housing enjoys a multilateral functioning in the rural system. One of the aspects highlighted by planning system is the renewal and rehabilitation of housing. In our country, Iran, development of rural housing has experienced a growing trend, especially in the physical and structural aspects. However, a large part of the rural population in different areas of the country is living in non-resistant and less durable housing. This article attempts to analyze the spatial distribution and quality of rural housing in the country. In this article it is tried to address and analyze the spatial distribution of quality and construction of rural housing in various provinces in the country. The data was derived from document studies. The quality of rural housing in 9 indices has been measured for each province of the country. Data has been analyzed using VIKOR method for the multi-criteria decision analysis. Finally, the classification of provinces based on the construction and quality of rural housing was conducted using K cluster analysis in SPSS and output was drawn in GIS as a map. The results showed that there is a significant difference and distinction in the types of materials used in the rural settlements. Such that a significant percentage of the houses are made out of bricks, iron and stone that somehow confirms the durability and normal quality. In terms of spatial and local distribution it can also be said that the quality of rural housing in most of the provinces (i.e. 24 provinces) are in low-quality, medium and/or appropriate levels. Meanwhile, only three provinces of Mazandaran, Azerbaijan Sharghi and Kerman enjoy the excellent quality in rural housing construction.